Hansen's disease in the era of COVID‐19: An observation on a series of six patients with co‐infection. Issue 2 (4th February 2021) - Arora, Sandeep; Bhatnagar, Anuj; Singh, Gautam Kumar; Pal, Reetika; Bahuguna, Amit; Das, Pankaj; Verma, Prachi
Abstract: Since the onset of the present pandemic, effect of the novel corona virus on other infectious conditions continues to be investigated. Although the immunological responses to SARS‐Cov‐2 infection have been elaborated extensively, they fail to explain, variations in its clinical manifestations and its interaction with other diseases. Hansen's disease is known to present as a complex immunological response to the lepra bacilli, resulting in its varied spectral manifestations. An interaction between these two infectious agents, hence, may affect Hansen's disease. We came across six cases of Hansen's disease who developed COVID19 co‐infection. This series presents their clinical course and outcome, during the period of co‐infection. All cases were followed up for a minimum eight‐week period thereafter. In all these cases the active phase of coronavirus infection had no effect on Hansen's disease and those on prednisolone for their lepra reaction had a more favorable outcome, with two cases manifesting exacerbation of their lepra reactions in the follow period.